Exploring small energy scales with x-ray absorption and dichroism - Praetorius, Christian Michael; Haverkort, Maurits W. (Physical review, 2016)
Soft x-ray linear and circular dichroism (XLD, XMCD) experiments at the Ce M4,5 edges are being used to determine the energy scales characterizing the Ce 4f degrees of freedom in the ultrathin ordered surface intermetallic CeAgx/Ag(111). We find that all relevant interactions, i.e., Kondo scattering, crystal field splitting and magnetic exchange coupling occur on small scales. Our study demonstrates the usefulness of combining x-ray absorption experiments probing the temperature dependence of both linear and circular dichroism owing to their strong sensitivity for anisotropies in both charge distribution and paramagnetic response, respectively.
Gesehen am 20.09.2017